What effect do point of care fees have on childhood consultations in general practice? - Andrew O'Regan; Walter Cullen; Clodagh O'Gorman; Louise Hickey; Eimear O'Neill; Jane O'Doherty; Ailish Hannigan (BMC, 2018)
Abstract Background General practice (GP) has historically been central to the prevention and treatment of childhood illnesses. In Ireland, this role has recently expanded with the introduction of free GP care for children aged under six years in 2015. The Republic of Ireland has the only health system in the European Union which does not offer universal coverage for primary care. This study aims to analyse general practice records to investigate the effect of point of care consultation fees on childhood attendances. Methods GPs affiliated to the medical school (n = 72) were invited to participate. 100 children aged 1 to 14 years were randomly sampled from each. Data was collected on service utilisation in the previous 12 months, specifically: age, gender, eligibility for free care and whether they had consulted their GP in the 12 month period. Results Sixty-four practices participated, producing data on 6007 eligible children. The median age of children was seven years; 3688(62%) were 'fee-paying'. GMS patients aged under six years had a median of three consultations/year, with a quarter attending six times a year or more, while fee paying patients had a median of two consultations/year with a quarter attending four times a year or more. Conclusions Children eligible for free care attend more often with a subgroup attending very frequently. This study provides important information on the possible impact of fees on healthcare utilisation for countries considering co-payment.